2017
DOI: 10.1021/acsami.7b13179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amidogen Functionalization on Quantum Spin Hall Effect in Bi/Sb(111) Films

Abstract: Knowledge about chemical functionalization is of fundamental importance to design novel two-dimensional topological insulators. Despite theoretical predictions of quantum spin Hall effect (QSH) insulator via chemical functionalization, it is quite challenging to obtain a high-quality sample, in which the toxicity is also an important factor that cannot be ignored. Herein, using first-principles calculations, we predict an intrinsic QSH effect in amidogen-functionalized Bi/Sb(111) films (SbNH and BiNH), charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 67 publications
(103 reference statements)
3
69
0
Order By: Relevance
“…The search for a new member of the Dirac SGS family with the QAHE is of great importance for both fundamental interest and practical applications. Also, QSHE has been reported in previously studies 25,36 . The layered crystals of transition-metal trichloride, and the family of layered materials with the general formula TMX 3 (TM = Ti, V, Cr, Fe, Mo, Ru, Rh, Ir) and X is a halogen anion (X = Cl, Br, I) have become of interest for this purpose.…”
supporting
confidence: 56%
“…The search for a new member of the Dirac SGS family with the QAHE is of great importance for both fundamental interest and practical applications. Also, QSHE has been reported in previously studies 25,36 . The layered crystals of transition-metal trichloride, and the family of layered materials with the general formula TMX 3 (TM = Ti, V, Cr, Fe, Mo, Ru, Rh, Ir) and X is a halogen anion (X = Cl, Br, I) have become of interest for this purpose.…”
supporting
confidence: 56%
“…As applying strain is another effective approach to regulate the electronic structures of 2D materials; the band gap, Schottky barrier height, and topological states can be effectively tuned. Therefore, the in‐plane strain was applied to modulate the electronic properties of Janus MoSSe/WX 2 heterostructures. In‐plane biaxial strain, ϵ , on the heterostructures was applied by varying the cell parameter as a = ( ϵ + 1) × a 0 , where a 0 is the equilibrium lattice constant and a is strained lattice constant.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum nontrivial band gap of 2D AsO can be enhanced from 89 to 130 meV under biaxial strain . Chemical functionalization is an effective approach to tailor the electronic and topological properties of 2D materials . The Janus structure can also be obtained by asymmetric functionalization of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…[74][75][76][77] Additionally, strain induced quantum spin Hall insulators 52 and giant and tunable Rashba spin splitting 53 from monolayers of SbBi binary compounds in buckled hexagonal structures have been predicted. Li et al showed that Bi(110) films 78 and amidogen modified Bi/Sb(111) films 79 are ideal platforms of the QSH effect for low-power dissipation devices. While interesting and fundamental effects were unveiled for 2D SbBi binary compounds, the chains of binary compounds of group-VA elements gained importance.…”
Section: Periodic Chains Of Group-va Binary Compoundsmentioning
confidence: 99%